Estimating Late 19th Century Hydrology in the Greater Everglades Ecosystem: An Integration of Paleoecologic Data and Models - Marshall, Frank E.; Bernhardt, Christopher E.; Wingard, G. Lynn (Frontiers in Environmental Science, 2020)
Restoration of the Greater Everglades Ecosystem requires an understanding of the hydrology of the natural system prior to significant alterations due to water management and land use. Large scale models such as the Natural Systems Model (NSM 4.6.2) have been used by the South Florida Water Management District and other agencies responsible for restoration to estimate past hydrologic conditions; however, these models typically portray a drier natural system for the beginning of the 20th century than what is indicated by paleoecologic analyses and historical data. The purpose of this study is to estimate pre-20th century water levels, hydroperiods and flow in the freshwater wetlands of the Everglades by using pollen assemblage data in three sediment cores to adjust the Natural Systems Model. This study is designed to further test estimates of flow through the Everglades derived from analysis of sediment cores collected in Florida Bay. The results demonstrate that the NSM 4.6.2 underestimates water levels and hydroperiods in the Everglades compared to the paleo-adjusted NSM 4.6.2 model outputs. Flow models that use the paleo-adjusted water levels as input indicate flow through Shark River Slough in the late 19th century was approximately two times observed levels, and flow through Taylor Slough was approximately three times observed levels. The flow estimates derived from this study agree with the estimates derived from earlier studies using estuarine cores.